(untitled) (8gen-ART, 2023)
The effect that the art the 20th century created brings a quest for a brand-new language in every field of the history of art and thought as well as performing arts. Until then, stage design was discussed as an equivalent of the visual world which was on the first page of the play, and which described the place in a literary way. And the unity of time and place was bounded by entrenched rules from Aristotle’s Poetics. A secondary space located in the rectangular and dark room of the theatre building; the setting served as a representation of the place no matter how realistic it was and was described as an illusion. Whereas the content of the modern art cut its ties with the past by rejecting all traditional codes. As the movements that occurred in modern art and sculpture created manifestos against each other, the history of the emancipation of art was written in a sense. Therefore, instead of the hierarchy of actor and text that is on the first layer between theatre and the audience, an expression of the text in a plastic language was tried. Since a total change could not occur altogether, changes occurred in: at first, the function of theatre buildings (the architectural structure) and thereby the limits of the area of the audience and the play, and then the actor’s subjective relation with their body and language, the questioning of content and form of the text, the use of setting and costume as an independent expression, all these developments occurred with the productions of extraordinary artists of the avant-garde art in the field of stage design. Today, considering the stage designs that were specifically made by many artists that are renowned worldwide in their own field, these are the most exclusive productions of theatre history. The article focus on the first quarter of the 20th century and in line with kind of a stage aestehetic the artist created and also the relationship and the design of abstract place tahat is created on stage, and it will present how this turned into a space research in the history scenography.